Dredd [videorecording (DVD)] - Travis, Pete; Urban, Karl, 1972-; Thirlby, Olivia, 1986-; Headey, Lena; Harris, Wood, 1969-; Kirkwood, Langley, 1973- (Lionsgate, 2013)
The future America is an irradiated wasteland. On its East Coast lies Mega City One, a vast, violent metropolis where criminals rule the chaotic streets. The only force of order lies with the urban cops called Judges who possess the combined powers of judge, jury and instant executioner.